Acute malnutrition and food insecurity in Yemen, 2021: Evidence from a two-stage cluster randomised survey in a protracted crisis. - Mariana Perez Duque; Abdulwahab Alburhomy; Ali Ahmed; Yousef Saleh; Anja Wolz; Ana B Abecasis; Neil J Saad Duque; Henrik Salje; Julita Gil-Cuesta; Jo Robays; Raphael Veicht; Saleem Alazab (PLOS Global Public Health, 2025)
The ongoing conflict in Yemen, which began in 2014, has led to one of the world's most severe humanitarian crises. The Hudaydah region, located on the Red Sea coast and home to the country's second-largest port, is critical for the delivery of food and medical supplies. We conducted a two-stage cluster randomised survey to estimate the prevalence of acute malnutrition among children and pregnant and lactating women (PLW). We estimated the prevalence of household food insecurity and quantified death rates. During February-March 2021, acute malnutrition prevalence was 14.1%(95%CI: 12.2-16.2) among children aged 6-59 months, with 4.0%(95%CI: 3.3-4.9) severely malnourished. 43% of malnourished children were not in a nutritional programme. Acute malnutrition among PLW was 25.7%(95%CI: 23.0-28.6). We estimated 54%(95%CI: 44-63) of households were food insecure, 22%(95%CI: 15-31) severely. Crude and under-five death rates were below humanitarian thresholds. More than half of the children reported sickness in the last 14 days, and this proportion was higher among the malnourished.